Debt and Pledge Verses in the Holy Quran: An Objective Inimitable Study - Freihat, Shareefah Abedulkareem (Journal of Islamic Sciences, 2019)
This study shows the legislative miracles in Ayah Debt and Ayah Mortgage and also it shows the accuracy of the Koran in the issues which is related to religious questions of Mortgage. The study dealt with the issue of writing the debt and the related rules for the debtor, lender and the writer of the debt; therefore, the right will not be lost and to achieve the goal of the act of debt which is gain the good form God and even not regret for debiting and lose reward from God. So, the debtor should state and recognize the right to give back the lender his money in the agreed time. At the same time, the Ayah stated the right of the debtor not to be exploited for his weakness or for his weak needs. As it stated also the indications that are harmful to the debtor from his or her inability to payback the debt, there are those who represent the debtor to payback the debt. The second topic discusses the issue that; in order to increase the creditability and guardianship and the preservation of rights, the verses stated the issue of witness, witnesses are either two men or men and two women and in view of the testimony of two women modify the testimony of one man which is very wise: to take into account the status of women in forgetfulness commensurate with her high profession and mandate The Lord has her motherhood and caring for her children. The Ayah stated the importance of attendance of the witnesses when it is needed for the preservation of rights, if necessary. The third topic deals with the issue of trade and writing of trade and showing the similarity between debt and trade in the term and the possibility of ignorance or forgetfulness. In order to avoid the conflicts and problems writing and witness were applied too. To achieve balance in the control of rights, the Ayah came to emphasize the piety because it is the only deterrent to those who violate the Gods’ ordered. As for traveling, the situation is different in urban areas, the possibility of the availability of the writer and the witnesses is almost weak, consequently to protect the rights in debt and trusteeship is discussed in the fourth topic. The mortgage is a means of preserving the rights and be away from conflicts and dispute. On the other hand; in the case trusteeship were it must be given to a trustful person, and the in case of payback the debt without writing or certification or mortgage; the fear of God is enough to justify the rights.